Mutation analysis of the cross-reactive epitopes of Japanese encephalitis virus envelope glycoprotein - Chiou, Shyan-Song; Fan, Yi-Chin; Crill, Wayne D.; Chang, Ruey-Yi; Chang, Gwong-Jen J. (Journal of general virology, 2012)
Group and serocomplex cross-reactive epitopes have been identified in the envelope (E) protein of several flaviviruses and have proven critical in vaccine and diagnostic antigen development. Here, we performed site-directed mutagenesis across the E gene of a recombinant expression plasmid that encodes the Japanese encephalitis virus (JEV) premembrane (prM) and E proteins and produces JEV virus-like particles (VLPs). Mutations were introduced at I135 and E138 in domain I; W101, G104, G106 and L107 in domain II; and T305, E306, K312, A315, S329, S331, G332 and D389 in domain III. None of the mutant JEV VLPs demonstrated reduced activity to the five JEV type-specific mAbs tested. Substitutions at W101, especially W101G, reduced reactivity dramatically with all of the flavivirus group cross-reactive mAbs. The group and JEV serocomplex cross-reactive mAbs examined recognized five and six different overlapping epitopes, respectively. Among five group cross-reactive epitopes, amino acids located in domains I, II and III were involved in one, five and three epitopes, respectively. Recognition by six JEV serocomplex cross-reactive mAbs was reduced by amino acid substitutions in domains II and III. These results suggest that amino acid residues located in the fusion loop of E domain II are the most critical for recognition by group cross-reactive mAbs, followed by residues of domains III and I. The amino acid residues of both domains II and III of the E protein were shown to be important in the binding of JEV serocomplex cross-reactive mAbs.